2004
DOI: 10.1248/bpb.27.496
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Up- and Down-Regulated Genes in the Heart of Juvenile Visceral Steatosis Mice

Abstract: Juvenile visceral steatosis (JVS) mice, novel animal models of systemic carnitine deficiency, exhibit a remarkably increased number of mitochondria in their cardiac myocytes. To date, however, there has been no reported investigation of the molecular mechanism of this increased number of mitochondria. Here, we analyzed the gene expression profile from the hearts of JVS and control mice by Affymetrix GeneChip analysis representing 34323 genes. We found that 176 genes, containing 93 known genes and 83 novel gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For example, in humans, defects in the Na ϩ -carnitine cotransporter (Na ϩ -driven organic cation transporter 2 [OCTN2]) cause a cardiomyopathy characterized by cardiac lipid accumulation and hypertrophy (34). Similarly, mice with juvenile visceral steatosis (JVS) mouse mimics human systemic carnitine deficiency because mice with JVS have a spontaneous deficiency of OCTN2 that results in cardiac lipid accumulation and hypertrophy, as well as a 2-fold increase in cardiac mitochondrial area (45). Inhibition of CPT1 and acyl-carnitine synthesis in rats leads to cardiac hypertrophy (39), and mice deficient in long-chain acylCoA dehydrogenase (LCAD) (11) or very-long-chain acylCoA dehydrogenase (VLCAD) (17) also develop cardiac hypertrophy, increased mitochondrial biogenesis, and TAG accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in humans, defects in the Na ϩ -carnitine cotransporter (Na ϩ -driven organic cation transporter 2 [OCTN2]) cause a cardiomyopathy characterized by cardiac lipid accumulation and hypertrophy (34). Similarly, mice with juvenile visceral steatosis (JVS) mouse mimics human systemic carnitine deficiency because mice with JVS have a spontaneous deficiency of OCTN2 that results in cardiac lipid accumulation and hypertrophy, as well as a 2-fold increase in cardiac mitochondrial area (45). Inhibition of CPT1 and acyl-carnitine synthesis in rats leads to cardiac hypertrophy (39), and mice deficient in long-chain acylCoA dehydrogenase (LCAD) (11) or very-long-chain acylCoA dehydrogenase (VLCAD) (17) also develop cardiac hypertrophy, increased mitochondrial biogenesis, and TAG accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The mice used for this study were JVS mice produced by in vitro fertilization according to the method reported by Suenaga et al [23]. C57BL/6J mice (Clea Japan, Inc., Japan) served as normal controls.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Studies in the CUD mouse model suggest that tissue levels of carnitine are resistant to the effect of low plasma carnitine levels, 26 and there is a compensatory increase in the expression of other genes involved in fatty acid oxidation and mitochondrial metabolism. 27 In the CUD animal model, the compensatory increased expression of the carnitine palmitoyltransferase 1 gene is repressed with oral carnitine. 28 The NZ treatment experience is that there are difficulties with compliance in our adult CUD patients.…”
mentioning
confidence: 99%